Termodinámica de las fases β, β' y ζº en el sistema Ag-Zn. - Abriata, José P. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 1970)
Fil. Abriata, José P.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina